2012
DOI: 10.1002/ldr.2183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rainfall Erosion: Seedling Damage and Establishment Problems

Abstract: Physical damage is one of the main factors that cause seedling mortality in many ecosystems. However, the impact of physical damage due to rainfall erosion on seedling mortality is seldom investigated. In this study, we ask the following question: how does rainfall erosion influence seedling damage and establishment in the Loess Plateau region of China? Seedling damage and establishment experiments under different patterns of simulated rainfall were conducted. The seedling damage rate, damage type and growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 48 publications
0
34
0
1
Order By: Relevance
“…Cerdà & Garcıa‐Fayos () and Wang et al . () also found that small‐seed species suffered the highest rates of washing away when compared with large‐seed species. Furthermore, large seeds confer seedlings with a competitive advantage (Turnbull et al ., , ) particularly in systems that have become covered by grasses (41% of direct‐seeding cases, Figure ).…”
Section: Discussionmentioning
confidence: 84%
“…Cerdà & Garcıa‐Fayos () and Wang et al . () also found that small‐seed species suffered the highest rates of washing away when compared with large‐seed species. Furthermore, large seeds confer seedlings with a competitive advantage (Turnbull et al ., , ) particularly in systems that have become covered by grasses (41% of direct‐seeding cases, Figure ).…”
Section: Discussionmentioning
confidence: 84%
“…The role of erosion as an ecological driver that shapes the composition of plant communities had already been highlighted in previous studies in arid and semiarid environments (Guàrdia et al, 2000;GuerreroCampo andMontserrat-Martí, 2000, 2004;García-Fayos and Bochet, 2009;Bochet et al, 2009;Jiao et al, 2009). However, relatively little attention had been paid to the effect of erosion on seeds (mainly seed transport and germination) as compared to later stages of the plant life (seedlings and adult plants; de Luís et al, 2005;Tsuyuzaki and Haruki, 2008;Wang et al, 2014), even though seed stage is one of the most critical phases in vegetation development (García-Fayos and Cerdà, 1997).…”
Section: Seed Characteristicsmentioning
confidence: 99%
“…Today, the Loess Plateau plays a critical role on the food production and energy sources in Chinese national economic development, but severe soil erosion undermine the environmental sustainability of the Loess Plateau and degrade the livelihood of 104·2 million people who live there (Tang et al ., ; He et al ., ). Food cultivation on the Loess Plateau is exacerbating soil erosion, sedimentation of the Yellow River, and groundwater recession (Miao et al ., ; Gao et al ., ; König et al ., ; Wang & Shao, ; Wang et al ., ; Zhao et al ., ).…”
Section: Introductionmentioning
confidence: 97%